2019
DOI: 10.3390/molecules24020220
|View full text |Cite
|
Sign up to set email alerts
|

9-Norlignans: Occurrence, Properties and Their Semisynthetic Preparation from Hydroxymatairesinol

Abstract: Lignans, neolignans, norlignans and norneolignans constitute a large class of phenolic natural compounds. 9-Norlignans, here defined to contain a β–β’ bond between the two phenylpropanoid units and to lack carbon number 9 from the parent lignan structure, are the most rarely occurring compounds within this class of natural compounds. We present here an overview of the structure, occurrence and biological activity of thirty-five 9-norlignans reported in the literature to date. In addition, we report the semisyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…1 H, 13 C, DEPT 45 • , DEPT 90 • , DEPT 135 • , COSY, NOESY, HSQC, and HMBC NMR data are shown in Table 1, while COSY, NOESY, and HMBC correlations are shown in Figure 2. The 1 H and 13 C data of 2 are in agreement with the literature, which confirmed that 2 was a 9,9 -bisnorlignan, 5,7,8-trimethoxy-1-(2,4,5-trimethoxyphenyl)-1,2-dihydronaphthalene or pachypostaudin B [35,36].…”
Section: Isolation and Identification Of Compounds From P Pellucida supporting
confidence: 88%
“…1 H, 13 C, DEPT 45 • , DEPT 90 • , DEPT 135 • , COSY, NOESY, HSQC, and HMBC NMR data are shown in Table 1, while COSY, NOESY, and HMBC correlations are shown in Figure 2. The 1 H and 13 C data of 2 are in agreement with the literature, which confirmed that 2 was a 9,9 -bisnorlignan, 5,7,8-trimethoxy-1-(2,4,5-trimethoxyphenyl)-1,2-dihydronaphthalene or pachypostaudin B [35,36].…”
Section: Isolation and Identification Of Compounds From P Pellucida supporting
confidence: 88%
“…NMR solvents were purchased from VWR Chemicals (CD 3 OD, CDCl 3 ). All norlignan substrates were synthesized from the natural lignan hydroxymatairesinol at Johan Gadolin Process Chemistry Center, Åbo Akademi University [9]. The [MoO 2 (SAP)] 2 and [MoO 2 (SATP)] 2 complexes were synthesized according to published procedures at the IUT-LCC, Castres.…”
Section: Methodsmentioning
confidence: 99%
“…The prefix "nor" indicates the lack of one or more carbon in the parent skeleton, and the term 9-norlignan is used when the lignan structure lacks C-9 (or γ carbon). As lignans, norlignans are also found in plants, having a range of biological activity [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographically, the intakes are greater in the European population relative to the Asian population (Bhakta et al, 2006). The main common dietary lignans are secoisolariciresinol, lariciresinol, matairesinol, pinoresinol, medioresinol, and syringaresinol (Durazzo et al, 2018); the range of components is very wide and efforts on isolation of new compounds are being carried out (Eklund and Raitanen, 2019;Xiao et al, 2019). Plant lignans are metabolized to enterodiol and enterolactone, called enterolignans or mammalian lignans (Landete, 2012).…”
Section: Introductionmentioning
confidence: 99%